The sustainability of solid waste management from the perspective of policy: towards a sustainable solid waste management in Kota Kinabalu - Haidy Henry Dusim (2018)
Ideally, analysing the sustainability of solid waste management system should not only be done purely from the perspective of technology, since according to the concepts of Integrated Sustainable Solid Waste Management (ISWM), the sustainability of solid waste management system can be influenced by other aspects such as policy, social, economy, environment, and institution. Although the issue of sustainable solid waste management system in the developing countries are commonly associated with the aspect policies, there are still limited studies conducted towards analysing the sustainability of solid waste management system from the perspective of policy. Hence, this study aims to analyse the sustainability of solid waste management system from the perspective of policy. In this study, Kota Kinabalu, Sabah was selected as a case study. This study employed both qualitative and quantitative approaches. The quantitative approach was mainly employed to support the data collected from the qualitative approach. In this study, data were mainly collected through the secondary data, interviews and questionnaires. Data collected from the interviews and secondary data were analysed using the thematic analysis. Meanwhile, data collected from the questionnaires were analysed using the statistical software called IBM Statistical Package for Social Science (SPSS) 21.1. The main findings of the study demonstrated that the existing solid waste management in Kota Kinabalu is still not sustainable since it lacks the aspect of adequate policies, adequate legislation, and strong regulations. Through this study, it significantly helps to shift the present studies from focusing on analysing the sustainability of solid waste management system purely from the perspective of technology to the policy perspective as this study has demonstrated that issues of solid waste are not purely technical. Moreover, through this study, it helps to uncover the important aspects that are required towards a sustainable solid waste management specifically from the perspective of policy. Additionally, this study indirectly helps to provide the future researchers or local governments guidelines to analyse the sustainability of solid waste management from the perspective of policy which in turns provide them valuable information towards developing a sustainable solid waste management particularly from the perspective of policy.